Efektivitas Model Problem Based Learning dalam Meningkatkan Pemahaman Fiqih Siswa Kelas XI MA Plus Anas Bin Malik Lekong Rembuk - Lalu Sidratul Muntaha Mawardi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to examine the effectiveness of the problem-based learning model (PBL) in improving the understanding of fiqh material and its implementation in class XI students of MA Plus Anas Bin Malik Lekong Rembuk. The PBL model was chosen because it is considered capable of encouraging active student involvement and developing critical thinking skills through solving real problems that are relevant to everyday life. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, each consisting of the planning, implementation, observation, and reflection stages. Data collection techniques include tests, observations, and interviews. The results of the study showed a significant increase in the understanding of fiqh concepts and active participation of students during the learning process. Students became more enthusiastic, able to express opinions, and demonstrate the ability to apply fiqh values in everyday life. Thus, the PBL model has proven effective in improving the quality of fiqh learning in madrasas and can be used as an alternative innovative learning strategy to improve learning outcomes and student character simultaneously.